Beta-Adrenergic Blockade Therapy for Autonomic Dysfunction is Less Effective for Elderly Patients with Heart Failure and Reduced Left Ventricular Ejection Fraction - Shimamoto, Ken (Jpn Clin Med, 2015)
OBJECTIVE: Heart rate variability (HRV) has been reported to be an independent predictor of all-cause and sudden cardiac death in patients with heart failure. In the aging heart, however, both autonomic and cardiac functions appear to be altered. We assessed the relationship between aging and responsiveness of HRV and ventricular remodeling to beta-adrenergic blockade therapy in patients with heart failure and reduced ejection fraction (HFREF). METHODS: Twenty-eight clinically stable patients with chronic heart failure, sinus rhythm, and left ventricular ejection fraction <50% as confirmed by echocardiography were included. At baseline and after carvedilol treatment, 24-hour ambulatory Holter monitor recording was used to analyze HRV indices by the maximum entropy method. Changes in these parameters were compared among three age groups. RESULTS: HR decreased in all groups after carvedilol treatment, but was still highest in the youngest group despite the same treatment doses. Time and frequency domain variables improved. The response of time domain variables (the standard deviation of all normal sinus to normal sinus [NN] intervals and the standard deviation of the averages of NN intervals in all 5-minute or 30-minute segments) to carvedilol therapy significantly decreased with increasing age. Ventricular reverse remodeling induced by carvedilol therapy significantly decreased with increasing age. Increases in time domain variables and a low-frequency domain moderately correlated with left ventricular reverse remodeling. CONCLUSION: Beta-adrenergic blockade therapy improved HRV variables and ventricular remodeling in HFREF patients; however, the response tended to be milder in the elderly. HRV improvement was associated with ventricular reverse remodeling.